2015
DOI: 10.1007/s00726-015-1926-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of d-aspartate in mammals: the rat and human homologs of mouse aspartate racemase are not responsible for the biosynthesis of d-aspartate

Abstract: D-Aspartate (D-Asp) has important physiological functions, and recent studies have shown that substantial amounts of free D-Asp are present in a wide variety of mammalian tissues and cells. Biosynthesis of D-Asp has been observed in several cultured rat cell lines, and a murine gene (glutamate-oxaloacetate transaminase 1-like 1, Got1l1) that encodes Asp racemase, a synthetic enzyme that produces D-Asp from L-Asp, was proposed recently. The product of this gene is homologous to mammalian glutamate-oxaloacetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Moreover, we observed that acute D-Asp administration also elicits a transient increase of extracellular L-Asp, without affecting the amount of this L-amino acid in homogenates. To explain this data, we suggest that abnormal accumulation of D-Asp in the brain may perturb one or more of the still unclear cellular mechanisms regulating the local racemization of D-Asp into L-Asp2829, L-Asp vesicular storage3031 and release32. In addition, we cannot exclude that non-physiological, high D-Asp extracellular concentration may displace L-Asp from its binding to L-Glu/L-Asp transporters, which regulate the uptake of both Asp enantiomers33, thus resulting in increased extracellular L-Asp levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed that acute D-Asp administration also elicits a transient increase of extracellular L-Asp, without affecting the amount of this L-amino acid in homogenates. To explain this data, we suggest that abnormal accumulation of D-Asp in the brain may perturb one or more of the still unclear cellular mechanisms regulating the local racemization of D-Asp into L-Asp2829, L-Asp vesicular storage3031 and release32. In addition, we cannot exclude that non-physiological, high D-Asp extracellular concentration may displace L-Asp from its binding to L-Glu/L-Asp transporters, which regulate the uptake of both Asp enantiomers33, thus resulting in increased extracellular L-Asp levels.…”
Section: Discussionmentioning
confidence: 99%
“…D-Asp is synthesized endogenously where it is needed from L-Asp by an aspartate racemase (27). In amphibian testis, the changes of this enzyme are significant, and racemase activity peaks in the reproductive period when D-Asp peaks testosterone levels are the highest during spermatogenesis and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…26,29,46,54 Employing multiple analytical techniques to measure the same analytes from the same samples can provide greater confidence for such measurements. 62 Unfortunately, these ancillary approaches are not always effective for single cell measurements.…”
Section: Discussionmentioning
confidence: 99%
“…27 Follow-up work on rat and human homologs of GOT1L1 suggest it may not be the mammalian source of D-Asp. 46 …”
mentioning
confidence: 99%